Macular neovascularisation in a patient with osteogenesis imperfecta exhibiting a novel COL1A1 mutation. Issue 11 (7th November 2022) - Sato, Yoshiki; Kimoto, Kenichi; Takaki, Yasuhiro; Kubota, Toshiaki
Abstract : Osteogenesis imperfecta is a congenital disease that presents with varying degrees of connective tissue symptoms, including susceptibility to fracture, growth disorders and hearing loss. Here, we discuss a case in which macular neovascularisation (MNV) resulted in metamorphopsia and decreased visual acuity in a patient with osteogenesis imperfecta exhibiting a novel COL1A1 gene mutation (p.Tyr165*). The patient was a woman in her 30s who reported experiencing distorted vision and diminished visual acuity in her right eye for 1 month as well as a history of hearing loss. Rapid improvements in exudative changes and suppression of relapse were achieved after only two intravitreal injections of ranibizumab. Furthermore, since MNV occurred slightly inferior to the fovea centralis, improvements in visual acuity were better than previously reported. As fragility of Bruch's membrane represents the basis of onset, recurrence and relapse are likely in patients exhibiting MNV, highlighting the need for regular follow-up.